Short Communication: Conservation of mangrove gobies in Lesser Sunda Islands, Indonesia - YULIADI ZAMRONI; KADARWAN SOEWARDI; BAMBANG SURYOBROTO; ZEEHAN JAAFAR (Society for Indonesian Biodiversity, 2016)
Zamroni Y, Soewardi K, Suryobroto B, Jaafar Z. 2016. Short Communication: Conservation of mangrove gobies in LesserSunda Islands, Indonesia. Biodiversitas 17: 553-557. Ecosystems goods and services from mangrove forests are especially vital to coastal communities. Yet mangrove areas continue to be deforested at unprecedented rates. Using gobioid fishes associated with mangrove forests as focal organisms, we assessed their diversity in 14 selected sites within the Lesser Sunda group of islands. We applied Correspondence analysis to determine the relationships between ecosystems based on the occurrence of these fishes and complementarity analysis to identify the minimum number of sites to conserve maximum diversity based on a rarity algorithm. We recovered 55 gobioid fish species at these mangrove areas, and proposed six mangrove areas within the Lesser Sunda group of islands as areas of conservation priority: Loh Sebita, Oebelo, Bipolo, Lembar Bay, Selindungan, and Kawangu. The three former areas are already within protected zones while the remaining latter three areas are at present unprotected. The argument for the conservation of these threeremaining areas is a compelling one, based on our data (diversity of gobioid fishes), and corroborating data (diversity of corals, reef fishes, stomatopods, seagrasses, and marine birds) from other studies.Keywords: Brackish, mangroves, deforestation, Nusa Tenggara, Threatened Species, Gobiidae